Tumor-neutrophil crosstalk promotes in vitro and in vivo glioblastoma progression - Rubenich, Dominique S.; de Souza, Priscila O.; Omizzollo, Natalia; Aubin, Mariana R.; Basso, Paulo J.; Silva, Luisa M.; da Silva, Eloisa M.; Teixeira, Fernanda C.; Gentil, Gabriela F.S.; Domagalski, Jordana L.; Cunha, Maico T.; Gadelha, Kerolainy A.; et al. (Frontiers in Immunology, 2023)
The tumor microenvironment (TME) of glioblastoma (GB) is characterized by an increased infiltration of immunosuppressive cells that attenuate the antitumor immune response. The participation of neutrophils in tumor progression is still controversial and a dual role in the TME has been proposed. In this study, we show that neutrophils are reprogrammed by the tumor to ultimately promote GB progression. Using in vitro and in vivo assays, we demonstrate the existence of bidirectional GB and neutrophil communication, directly promoting an immunosuppressive TME. Moreover, neutrophils have shown to play an important role in tumor malignancy especially in advanced 3D tumor model and Balb/c nude mice experiments, implying a time- and neutrophil concentration-dependent modulation. Studying the tumor energetic metabolism indicated a mitochondria mismatch shaping the TME secretome. The given data suggests a cytokine milieu in patients with GB that favors the recruitment of neutrophils, sustaining an anti-inflammatory profile which is associated with poor prognosis. Moreover, clinical samples have indicated that neutrophil-lymphocyte ratio (NLR), IL-1β, and IL-10 are associated with poor outcomes in patients with GB. These results are relevant for understanding how tumor progression occurs and how immune cells can help in this process.